Directions For Improving State Migration Policy and Uniformity - Israilova Dilfuza Karimovna (Genius Journals, 2022)
This article talks about state regulation of labor migration, directions for effective migration policy implementation
Keywords: Labor market; labor migration; informal migration; incentive policy